BUYING AND SELLING STOCKS TRANSACTIONS OF CHILDREN’S IN THE PERSPECTIVE OF SHAFI’I SCHOLARS - Faisal, Faisal; Al Faerah, Putri Alya Zuhra (Program Studi Manajemen Keuangan Syariah, 2025)
This study explores the Shafi’i jurisprudential perspective, particularly regarding the buying and selling of shares by children who are still underage. The buying and selling of shares constitutes a social enterprise or cooperation between two or more shareholders with a specific purpose, wherein each party contributes funds with the promise that they will share both profits and risks collectively. Through this, the researcher hopes to provide benefits and serve as a reference for shareholders. The research method employed is field research, which encompasses all occurrences in the field to extract and examine data relevant to the study. The approach taken in this research utilizes qualitative research methods. Based on the conclusions of this study, from the perspective of the Shafi’i school of jurisprudence, the buying and selling of shares conducted by a child who is still underage or has not yet reached puberty falls into the category of being discouraged or invalid, even if it is permitted by their parents or guardians.